2021
DOI: 10.3389/fphar.2021.743623
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Traditional Chinese Medicine Against Respiratory Viruses: A Review

Abstract: Respiratory viruses, such as severe acute respiratory syndrome coronavirus (SARS-CoV)-1, SARS-CoV-2, influenza A viruses, and respiratory syncytial virus, pose a serious threat to society. Based on the guiding principles of “holism” and “syndrome differentiation and treatment”, traditional Chinese medicine (TCM) has unique advantages in the treatment of respiratory virus diseases owing to the synergistic effect of multiple components and targets, which prevents drug resistance from arising. According to TCM th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 135 publications
(134 reference statements)
0
18
0
Order By: Relevance
“…Further study will be needed for characterizing the mechanism for whole body and reproductive organs such as uterus and ovary. Third, although Sho in Kampo and Zheng in TCM were derived from the same word, they have acquired different meanings ( 7 , 20 22 ). In this case report, it should be noted that we described Sho in Kampo.…”
Section: Discussionmentioning
confidence: 99%
“…Further study will be needed for characterizing the mechanism for whole body and reproductive organs such as uterus and ovary. Third, although Sho in Kampo and Zheng in TCM were derived from the same word, they have acquired different meanings ( 7 , 20 22 ). In this case report, it should be noted that we described Sho in Kampo.…”
Section: Discussionmentioning
confidence: 99%
“…These virucidal drugs were shown to possess potential virucidal activity in the small intestine against IBV (86). Traditional medicines, mainly from China, have been very effective against respiratory viruses (87). A combination effect of traditional Chinese medicines (TCMs), such as Shegandilong (SGDL) and doxycycline, was examined by Feng et al (88) to prevent viral infection, and the outcomes indicated an increased level of tracheal immunoglobulin A (IgA).…”
Section: Use Of Virucidal Drugs Against Ibv Infectionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has a long history of preventing and treating in uenza and exerts obvious advantages. [6,7]. Mosla scabra, belonging to the Lamiaceae family, is a perennial herb which has been used since the late Han Dynasty for treating and preventing lung and gut diseases, including in uenza virus, herpes simplex virus, allergy, and gastroenteritis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%